Home Resources, Job Crafting, dan Work Engagement sebagai Prediktor Job Performance Karyawan Café Dine-In - Daniel Christian B.; B Medina Nilasari; Dita Oki Berliyanti (JURNAL ECONOMINA, 2026)
The dine-in cafe industry faces high service demands, requiring employees with optimal performance. Employee job performance is influenced by various factors, both from the home environment and proactive work behavior. This study aims to analyze the influence of Home Resources and Job Crafting on Job Performance with Work Engagement as a mediating variable in dine-in cafe employees in Depok City. The study used a quantitative approach with a survey method on dine-in cafe employees selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4. The results showed that Home Resources and Job Crafting had a positive effect on Work Engagement. In addition, Work Engagement had a positive effect on Job Performance and was able to mediate the influence of Home Resources and Job Crafting on Job Performance. These findings indicate that support from the home environment and proactive behavior in shaping work can increase work engagement, thus impacting the performance of dine-in cafe employees. This research implies that café managers need to encourage the creation of a work environment that supports job crafting behavior while also addressing employee well-being to improve organizational performance. This abstract should be tailored to the objectives, variables, and research methods in your thesis.